2003
DOI: 10.1097/01.ta.0000067288.11456.98
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Injury to Restrained Children in Side Impact Motor Vehicle Crashes

Abstract: In this study population, side impacts resulted in more injuries to the head, cervical spine, and chest. Knowledge of this pattern-the side impact syndrome-can help guide diagnosis, treatment, and prevention strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…Second, children in lateral crashes had strikingly increased ISS scores and decreased GCS scores as compared with those in frontal crashes. This confirmed and supports earlier work from Orzechowski and others [7,10]. In this study, the side-impact syndrome was described.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Second, children in lateral crashes had strikingly increased ISS scores and decreased GCS scores as compared with those in frontal crashes. This confirmed and supports earlier work from Orzechowski and others [7,10]. In this study, the side-impact syndrome was described.…”
Section: Discussionsupporting
confidence: 94%
“…Thoracic injuries are associated with a high mortality, particularly in car crashes that occur in a remote environment. This observation supports prior work from a study by Orzechowski et al [7] with some new findings. In contrast to that study, which was performed on a smaller sample, ours did not find a statistically significant difference in cervical spine injuries in lateral-impact crashes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…[43] In the pediatric age group, the side impacts resulted in more injuries to the head, cervical spine, and chest than frontal impacts. [44] The Centre for Accident Research and Road Safety-Queensland (CARRS-Q), which analyzed over 30 000 Victorian crash records from 1993 to 2004, concluded that in a traffic crash, the risk of fatality for children aged 0-12 years was twice as high for children in the front seat compared to children in the back seat. [45] In contrast to forward-facing car seat (FFCS), a rear-facing car seat (RFCS) supports the child's head, preventing the relatively large head from loading the proportionately smaller neck.…”
Section: Risk Factorsmentioning
confidence: 99%